Medieval Norwich - Rawcliffe, Carole, 1946-; Wilson, R. G. (Richard George); ebrary, Inc. (London : Hambledon and London, 2004)
Throughout the middle ages, Norwich was one of the most populous and celebrated cities in England. Dominated by its castle and cathedral priory, it was the centre of government power in East Anglia, as well as an important trading entrepot. With records dating back to Anglo-Saxon times, and many buildings surviving from the middle ages, the history of medieval Norwich is an exceptionally rich one. Medieval Norwich is an account of the growth of the city, with its walls, streams, markets, hospitals and churches, and the lives of its citizens. It traces activities and beliefs, as well as the tensions lying not far beneath the surface that eventually erupted in Kett's Rebellion of 1549.
1, The Urban Landscape -- 2, Norwich before 1300 -- 3, The Churches -- 4, The Religious Houses -- 5, Glass-Painting -- 6, Religious Practice -- 7, Norwich before the Black Death -- 8, Order and Disorder -- 9, Trade -- 10, The Urban Elite -- 11, The Reformation -- 12, Kett's Rebellion -- 13, Sickness and Health
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: do 16. století; středověká města -- Anglie; středověká společnost -- Anglie; medieval cities and towns -- England; medieval society -- England; Norwich (Anglie) -- dějiny -- do 16. století; Norwich (England) -- history -- to 16th century; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online